2005
DOI: 10.2337/diacare.28.10.2497
|View full text |Cite
|
Sign up to set email alerts
|

Elevated C-Reactive Protein Is a Predictor of the Development of Diabetes in a General Japanese Population

Abstract: OBJECTIVE -We examined the association between high-sensitivity C-reactive protein (CRP) levels and the development of diabetes in a general Japanese population. RESEARCH DESIGN AND METHODS-A total of 1,759 Japanese subjects, aged 40 -79 years and without diabetes (according to American Diabetes Association fasting criteria), were stratified into three groups according to CRP tertiles by sex and followed up prospectively for a mean of 9.0 years.RESULTS -During the follow-up, 131 subjects (67 men and 64 women) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
119
6
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(136 citation statements)
references
References 22 publications
9
119
6
1
Order By: Relevance
“…In addition, recently published results from the cross-sectional Health, Aging and Body Composition Study demonstrated a significant sex interaction between levels of CRP and the presence of diabetes, impaired glucose tolerance, or impaired fasting glucose as determined by an oral glucose tolerance test in the age-, race-, and lifestyle-adjusted model and showed that CRP was not associated with diabetes or hyperglycemic status after further adjustment for physiologic risk factors in men but remained highly associated with the outcome in women (35). However, our results are in contrast with observations from the Hoorn Study, where CRP was only associated with diabetes in men but not in women (11) and with results from two Japanese populations, where an equally strong association between CRP and diabetes was seen in men and women (15,16). Furthermore, results of the present study are in contrast with those of the West of Scotland Coronary Prevention Study and the Kuopio Ischemic Heart Disease Risk Factor Study, both of which demonstrated an independent association between CRP and incident type 2 diabetes in men (7,14).…”
Section: Thorand and Associatescontrasting
confidence: 57%
See 3 more Smart Citations
“…In addition, recently published results from the cross-sectional Health, Aging and Body Composition Study demonstrated a significant sex interaction between levels of CRP and the presence of diabetes, impaired glucose tolerance, or impaired fasting glucose as determined by an oral glucose tolerance test in the age-, race-, and lifestyle-adjusted model and showed that CRP was not associated with diabetes or hyperglycemic status after further adjustment for physiologic risk factors in men but remained highly associated with the outcome in women (35). However, our results are in contrast with observations from the Hoorn Study, where CRP was only associated with diabetes in men but not in women (11) and with results from two Japanese populations, where an equally strong association between CRP and diabetes was seen in men and women (15,16). Furthermore, results of the present study are in contrast with those of the West of Scotland Coronary Prevention Study and the Kuopio Ischemic Heart Disease Risk Factor Study, both of which demonstrated an independent association between CRP and incident type 2 diabetes in men (7,14).…”
Section: Thorand and Associatescontrasting
confidence: 57%
“…This hypothesis has recently been supported by several prospective studies showing that subjects who developed type 2 diabetes during the follow-up period had elevated levels of markers of inflammation such as C-reactive protein (CRP) or interleukin (IL)-6 at baseline compared with subjects who did not develop the disease (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). However, although various studies have examined these associations, few reported sexspecific results (5,11,15,16). This lack of data is surprising, since there is strong evidence for sex differences in associations between diabetes, obesity, endogenous sex hormones, and inflammation (17)(18)(19)(20)(21).…”
mentioning
confidence: 55%
See 2 more Smart Citations
“…There is heterogeneity between studies, with some demonstrating an independently positive association of CRP with incident diabetes [3][4][5][6][7][8][9][10][11], while others show no association after adjustment for adiposity and insulin resistance [12][13][14][15]. Differences in the association between CRP and diabetes by sex have also been reported [16][17][18].…”
Section: Introductionmentioning
confidence: 99%